Effect of a Mediterranean Diet during Pregnancy on Fetal Growth and Preterm Delivery: Results From a French Caribbean Mother–Child Cohort Study (TIMOUN). Issue 3 (18th February 2014) - Saunders, Lauren; Guldner, Laurence; Costet, Nathalie; Kadhel, Philippe; Rouget, Florence; Monfort, Christine; Thomé, Jean‐Pierre; Multigner, Luc; Cordier, Sylvaine
Abstract Background Recent studies suggest that a Mediterranean dietary pattern during pregnancy may influence pregnancy outcomes. The aim of this study was to evaluate the effect of adherence to a Mediterranean diet (MD) during pregnancy on fetal growth restriction (FGR) and preterm delivery (PTD) in a French Caribbean island where the population is largely of African descent and presents dietary patterns similar to MD. Methods Using data from the TIMOUN Mother–Child Cohort Study conducted in Guadeloupe (French West Indies) between 2004 and 2007, we analysed data for 728 pregnant women who delivered liveborn singletons without any major congenital malformations. Degree of adherence to MD during pregnancy was evaluated with a semi‐quantitative food frequency questionnaire based on nine dietary criteria. Multiple logistic regression models were used to analyse birth outcomes while taking potential confounders into account. Results Overall there was no association between MD adherence during pregnancy and the risk of PTD or FGR. However, pre‐pregnancy body mass index was a strong effect modifier, and MD adherence was associated with a decreased risk of PTD specifically in overweight and obese women (adjusted odds ratio 0.7, 95% confidence interval 0.6, 0.9) (P heterogeneity <0.01). Conclusions These results suggest that Caribbean diet during pregnancy may carry some benefits of MD and may contribute to reduce the risk of PTD in overweight and obese pregnant women.